PENGARUH PEMBIAYAAN MURABAHAH, TABUNGAN WADI’AH DAN DEPOSITO MUDHARABAH TERHADAP PROFITABILITAS (ROA) PADA BANK NTB SYARIAH KANTOR PUSAT KOTA MATARAM: PENGARUH PEMBIAYAAN MURABAHAH, TABUNGAN WADI’AH DAN DEPOSITO MUDHARABAH TERHADAP PROFITABILITAS (ROA) PADA BANK NTB SYARIAH KANTOR PUSAT KOTA MATARAM - Azizoma, Rusman; Sumiati (Universitas Islam Negeri Mataram, 2023)
This study aims to determine the effect of murabahah financing, wadiah savings and mudharabah deposits on profitability (ROA) at NTB Syariah banks for the 2019–2021 period. This type of research is quantitative research using secondary data from the monthly financial reports of Bank NTB Syariah for the 2019-2021 period and analyzed and processed using SPSS. The results of this study indicate that murabahah financing has a significant effect on profitability (ROA) with a significant level of 0.00 <0.05. Wadiah savings have a significant negative effect on profitability (ROA) with a significant level of 0.002 <0.05. Mudharabah deposits have a significant effect on profitability (ROA) with a significant level of 0.025 > 0.05. an influence contribution of 89.7%.